Exercising the powers of local self-government agencies in Ukraine: The Need of Implementation International Standard - Fedorenko, Vladislav Leonidovich; Dniprov, Oleksii Serhiiovych; Panchyshyn, Ruslan; Muzychuk, Oleksandr Mykolaiovych (DIXI, 2021)
The notion of governance is fundamental in the management of every given society, and for this to be realized, there is that need in placing powers in the hands of it’s community for the proper enhancement of the community. In it’s plight of achieving credible development and potential Justice system, there that need of the local Self-Government agencies to be fully involved in the well-being of the society. It is therefore in this light that this article is explore to study and compare international experience in the area of local self-government agencies functioning, providing propositions on its implementation in Ukraine. International experience in exercising the powers by local self-government agencies is analyzed; offers concerning its adaptation in Ukraine are given. It is noted that local self-government agencies constitute an important component of the functioning and development of any country, but their impact on ensuring the rights, freedoms and legitimate interests of the community, addressing their pressing issues is one that needs improvement. The positive aspect of decentralization is also due to the shift of a significant part of administrative powers from the center to municipalities and local communities in society, especially in its progressive part, there is a real chance to implement those changes, at least at the local level, which are extremely necessary for a long period of time. Conversely, if the central authorities are endowed with the maximum amount of power and imperative powers, while leaving local self-government agencies a fairly narrow amount of real power, the development tendencies of such a state will be mostly negative. It was established that highly developed de-mocracies from the very beginning of their existence were clearly aware of the importance of decentralization of governance, as well as the need to protect and maintain a high level of independence of each administrative and territorial unit, consistently ensuring their rights and interests.